Controlled ballistics tests of ground, percussion-flaked, and pressure-flaked projectile point impact durability: Implications for archaeological method and theory. (April 2019) - Lowe, Corey; Kramer, Andrew; Wilson, Michael; Meindl, Richard; Spurlock, Linda; Eren, Metin I.
Abstract: Ground stone projectile points can be found throughout the global archaeological record, but why they were selected for by prehistoric foragers has received little attention. Additionally, modern archaeological experiments have increasingly used ground points in lieu of knapped ones. Here, we present an experiment testing whether there is a difference between ground, percussion flaked, and pressure flaked points in terms of impact durability. Our three groups were similar in form, raw material, and hafting, only differing in their production. Controlled ballistics tests demonstrated that ground stone points did not break at a different rate than either the percussion flaked or pressure flaked points, nor was post-firing point length (as a percentage of original point length) different. These results are consistent with the hypothesis that impact durability on its own was not likely a motivating factor for forager selection of grinding versus knapping. Instead, researchers should look to other factors, such as skill, demography, time budgets, or raw material selection to explain the emergence of ground stone points in particular contexts. Given our null results, our test also supports the use of ground stone points in modern archaeological experiments. Highlights: Ground stone projectile points are found throughout the global archaeological record. We compared ground, percussion flaked, and pressure flaked point impact durability. We found no significant differences among the three groups.